On species related to Elachista pollutella Duponchel (Lepidoptera, Elachistidae), with descriptions of four new Palaearctic species - Kaila, Lauri (Entomologica Fennica, 2011)
The taxonomy of the relatives of Elachista (Aphelosetia) pollutella Duponchel, 1843 is clarified. The following species are described as new: Elachista jubarella sp. n. from Russian Caucasus, Elachista rutjani sp. n. from Russia: South Ural and Tuva, and Ukraine, Elachista enochra sp. n. from Turkmenistan, and E. cretula sp. n. from Kazakhstan and Turkmenistan. E. pollutella, previously only known from Central and Southern Europe, is recorded for the first time from Asian part of Russia in Altai Mts. and Mongolia. The identity of Elachista ilicrina Falkovitsh, 1986 is discussed.